2015
DOI: 10.1002/pros.22956
|View full text |Cite
|
Sign up to set email alerts
|

Prostate‐specific membrane antigen‐based imaging in prostate cancer: Impact on clinical decision making process

Abstract: PSMA based nuclear imaging has significantly impacted our way of handling patients with prostate cancer. Its preliminary performance in different clinical scenarios and ability to detect lesions even in low PSA values seems fairly promising and deserves to be supplemented with further clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 26 publications
1
28
0
2
Order By: Relevance
“…By contrast, CT and MRI have low sensitivity for lymph node metastasis, with detection only of lesions >10 mm in diameter. Consequently, CT and MRI may fail to detect microscopic invasion of the lymph nodes [42,43]. In the present study, multiple lymph node involvements affecting the mediastinum, retroperitoneum and pelvis were detected in 8 patients using 68 Ga-PSMA-11 PET/CT, but were negative on CT and/or MRI.…”
Section: Discussionmentioning
confidence: 49%
“…By contrast, CT and MRI have low sensitivity for lymph node metastasis, with detection only of lesions >10 mm in diameter. Consequently, CT and MRI may fail to detect microscopic invasion of the lymph nodes [42,43]. In the present study, multiple lymph node involvements affecting the mediastinum, retroperitoneum and pelvis were detected in 8 patients using 68 Ga-PSMA-11 PET/CT, but were negative on CT and/or MRI.…”
Section: Discussionmentioning
confidence: 49%
“…Note that for the cohort used by Afshar-Oromieh et al [14], not all patients (91.5%) had disease recurrence; however, given that they were in the overwhelming majority, we included this study in the analysis. Where a range was reported by a study as a PSA category, we took the midpoint of this range as the reference point for the category except for Sachpekidis et al [42], Demirkol et al [31], and Kabasakal et al [37], who reported individual patient-level data and manually calculated the reference point. Note that in the study by Kabasakal et al, only two out of 13 secondary staging patients had PSA <2 ng/ml, so the whole cohort was categorised in the 2 ng/ml PSA subpopulation.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…One additional study was excluded as patients were enrolled following negative choline-based PET, and thus provided a skewed patient population [28]. This left 18 articles were suitable for assessment [14,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]; a summary of the search strategy is shown in Figure 1. On evaluation of predictive values for positive 68 Ga-PSMA PET, two studies included only patients with positive 68 Ga-PSMA PET findings and predictive data were not available for analysis [34,35].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Currently, there are no prospective data for the treatment of oligometastatic PC using PSMA PET for staging. However, a retrospective case collection of Demirkol et al describes significant therapy changes due to the high diagnostic value of 68 Ga-PSMA-PET [19]. …”
Section: Introductionmentioning
confidence: 99%